The, Effectiveness The Effectiveness of Slido as an Interactive Learning Medium for Asmaul Husna Material for Seventh Grade Students at MTs Berkah Palangka Raya: Analysis of grade VII students at MTs Berkah Palangka Raya - Sabilah Labibah; Jasiah Jasiah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was this study aimed to analyze the effectiveness of Slido as an interactive student response system platform in strengthening learning participation and memory reinforcement in the material of Asmaul Husna among seventh-grade students of MTs Berkah Palangka Raya. The development of digital learning technology drives Islamic Education (PAI) teachers to integrate interactive media that are more relevant, contextual, and engaging for the characteristics of the contemporary student generation. The presence of Slido is positioned not merely as a supporting media, but as a pedagogical resource that potentially restructures the dynamics of participation and interaction in religious learning. Through Slido, students have the opportunity to engage actively, respond anonymously, and increase their self-confidence in expressing answers and opinions. This research sought to portray this phenomenon empirically. Materials and methods. This research applied a qualitative descriptive approach, with the primary data obtained through structured interviews involving students who followed the learning using Slido. Data were collected through purposive sampling and analyzed using Miles & Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The instrument used was an interview guideline focusing on student perceptions, attention span, learning focus, and memory reinforcement aspects during Slido-based learning Results. The findings indicate that Slido increases learning focus, participation, student confidence in expressing opinions, and supports better memorization of Asmaul Husna compared to conventional lecture-based instruction. However, several limitations emerged, including unstable internet connectivity and limited device compatibility. Conclusions. Slido provides positive pedagogical implications for Asmaul Husna learning in madrasah settings, but requires adequate infrastructure support and teacher creativity to reach optimal effectiveness.